METODE ANALYTIC NETWORK PROCESS (ANP) UNTUK MENGANALISIS FAKTOR BELUM DITERAPKANNYA MUNICIPAL ISLAMIC BONDS PADA DAERAH BERPOTENSI SUKUK DI INDONESIA - Erma Sri Hastuti; Bedjo Santoso (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to analyze what factors affect has not been applied municipal islamic bondsin a potentially sukuk region in Indonesia. Previous research already exists that discusseswhich areas have the potential to publish municipal Islamic bonds but until now no region haspublished municipal islamic bonds. Whereas municipal Islamic bonds can cover the budgetdeficit of regional income and can finance the development of regional infrastructure so that noneed debt. Therefore, the authors do research what factors are the cause by using the methodof analytic network process to obtain the priority scale of the causal factor has not been appliedmunicipal islamic bonds in the area of potentially sukuk in Indonesia. From this research, itis found that there are two main problem that is internal and external problem. In the internalproblem which becomes the main factor is Human Resources being in external problem whichbecome the main factor is government regulation.Keywords: Analytic Network Process, Sukuk, Municipal Islamic Bonds